Synthesis and dopamine receptor binding of dihydrexidine and SKF 38393 catecholamine-based analogues - da Silva, Suzane Rosa [UNESP]; Kalaba, Predrag; Fabišiková, Anna; Zehl, Martin; Dragačević, Vladimir; dos Anjos, Luana Ribeiro [UNESP]; Neill, Philip John; Wieder, Marcus; Prado-Roller, Alexander; Gajic, Natalie; Palaretti, Vinicius; da Silva, Gil Valdo Jose; et al. (Springer Nature, 2022)
Dopamine is an important neurotransmitter that regulates numerous essential functions, including cognition and voluntary movement. As such, it serves as an important scaffold for synthesis of novel analogues as part of drug development effort to obtain drugs for treatment of neurodegenerative diseases, such as Parkinson's disease. To that end, similarity search of the ZINC database based on two known dopamine-1 receptor (D1R) agonists, dihydrexidine (DHX) and SKF 38393, respectively, was used to predict novel chemical entities with potential binding to D1R. Three compounds that showed the highest similarity index were selected for synthesis and bioactivity profiling. All main synthesis products as well as the isolated intermediates, were properly characterized. The physico-chemical analyses were performed using HRESIMS, GC/MS, LC/MS with UV–Vis detection, and FTIR, 1H NMR and 13C NMR spectroscopy. Binding to D1 and D2 receptors and inhibition of dopamine reuptake via dopamine transporter were measured for the synthesized analogues of DHX and SKF 38393.
Keywords: D1R agonists; D2R and DAT; Dihydrexidine; Dopamine analogs; SKF 38393